Personality traits and sexual self‐efficacy in diabetic women: The mediating role of marital satisfaction and sexual function. Issue 11 (23rd September 2021) - Jabbari, Masoumeh; Hosseini ‐Tabaghdehi, Monirolsadate; Kashi, Zahra; Mousavinasab, Nouraddin; Shahhosseini, Zohreh
Abstract: Introduction: Although the relationship between personality traits and sexual self‐efficacy has received theoretical and empirical support, there is little information on how personality affects the sexual self‐efficacy of diabetic women. This study aimed to investigate the mediating role of marital satisfaction and sexual function in the relationship between personality traits and sexual self‐efficacy in diabetic women. Methods: Using a two‐stage sampling method, 410 reproductive‐aged Iranian women with type 2 diabetes were recruited in this descriptive‐analytical study. The participants completed self‐administered questionnaires, including the Vaziri Sexual Self‐Efficacy Questionnaire, the Female Sexual Function Index, ENRICH Marital Satisfaction Scale, and the Goldberg's Big Five Questionnaire. To analyze the data, structural equation modeling was employed in Amos software version 24. Results: Results indicated an acceptable fit of the model to the data. Personality trait of openness to experience was associated with sexual self‐efficacy directly ( β = .02, p = .030) and indirectly through the mediators of marital satisfaction ( β = .06, p = .009) and sexual function ( β = .18, p = .014). Furthermore, sexual function was associated with sexual self‐efficacy directly ( β = .50, p = .025) and indirectly through the mediator of marital satisfaction ( β = .36, p = .012). Conclusion: Due to the mediating role of marital satisfaction and sexual function, this study has some practical implications for improving the sexual self‐efficacy of diabetic women with different personality traits. Abstract : The relationship between personality traits and sexual self‐efficacy has received theoretical and empirical support, although there is little information on how personality affects the sexual self‐efficacy of diabetic women.